Aztreonam-avibactam synergy, a validation and comparison of diagnostic tools - Verschelden, Gil; Noeparast, Maxim; Stoefs, Anke; Van Honacker, Eveline; Vandoorslaer, Kristof; Vandervore, Laura; Olbrecht, Margo; Van Damme, Kathleen; Demuyser, Thomas; Piérard, Denis; Wybo, Ingrid (Frontiers in Microbiology, 2023)
Antimicrobial resistance is a growing problem that necessitates the development of new therapeutic options. Cefiderocol and aztreonam (AT) are often the last active ß-lactams for treating metallo-ßlactamases (MBL)-producing Gram-negative bacilli. In these difficult-to-treat bacterial strains, AT resistance is frequently attributed to the co-occurrence of other resistance mechanisms. In the case of ß-lactamases they can often be inhibited by avibactam.In the present study, we evaluated the use of the double-disc synergy test (DDST) as a screening tool for the detection of synergy between AT-avibactam (ATA). We validated both the Gradient Diffusion Strips (GDSs) superposition method and the commercially available Liofilchem's ATA GDS.We tested AT susceptibility in combination with ceftazidime-avibactam for 65 strains, including 18 Serine-ß-Lactamase (SBL)-and 24 MBL-producing Enterobacterales, 12 MBL-producing P. aeruginosa, and 11 S. maltophilia isolates. Interpretation was done with EUCAST breakpoints (version 13.0), AT breakpoints being used for ATA. The accuracy and validity of the GDSs superposition method and ATA GDS were evaluated using an AT GDS applied on Mueller Hinton Agar plates supplemented with avibactam (MH-AV). A DDST was performed to screen for synergy between antibiotic combinations.Using MH-AV, all SBL-and MBL-positive Enterobacterales were susceptible or susceptible at increased exposure to the combination AT-avibactam. In contrast, only 2 out of the 12 (17%) P. aeruginosa strains and 9/11 (82%) of the S. maltophilia strains were susceptible-or susceptible at increased exposure for the combination of AT-avibactam. The DDST detected all synergies, demonstrating a 100% sensitivity and 100% negative predictive value for all bacterial strains.The DDST is a sensitive tool for screening for antibiotic synergy. Unlike S. maltophilia and SBL-and MBL-positive Enterobacterales, most MBL-positive P. aeruginosa strains remain resistant to AT-avibactam. ATA GDS should be preferred for MIC determination of the AT-avibactam combination, while the GDSs superposition method can be used as an alternative to the commercial test.